2009
DOI: 10.3146/ps08-020.1
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity in Transgenic Peanut (Arachis hypogaeaL.) Conferred by a Nonheme Chloroperoxidase Gene

Abstract: A nonheme chloroperoxidase gene (cpo-p) from Pseudomonas pyrrocinia, a growth inhibitor of mycotoxin-producing fungi, was introduced into peanut via particle bombardment. The expression of the cpo-p gene is predicted to increase pathogen defense in peanut. Embryogenic peanut tissues were bombarded with gold particles coated with plasmid pRT66 carrying the cpo-p and hygromycin phosphotransferase (hph) genes, under the control of a double CaMV 35S and a single CaMV 35S promoter, respectively. Selection for hygro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A nonheme chloroperoxidase gene (cpo-p) from Pseudomonas pyrrocinia, which converts reactive oxygen species, such as hydrogen peroxide into antimicrobial peracetic acid and hypohalites (Jacks et al, 2000;Van Pée, 1996), was introduced into peanut and cotton. In vitro bioassays using crude protein extracts from transgenic peanut and cotton plants and their progenies showed inhibition of A. flavus hyphal growth (Niu et al, 2009;Rajasekaran et al, 2008b). We have provided below examples of antifungal proteins and peptides showing efficacy in controlling A. flavus in maize.…”
Section: Enhancement Of Host Resistance Expression Of Antifungal Protmentioning
confidence: 96%
“…A nonheme chloroperoxidase gene (cpo-p) from Pseudomonas pyrrocinia, which converts reactive oxygen species, such as hydrogen peroxide into antimicrobial peracetic acid and hypohalites (Jacks et al, 2000;Van Pée, 1996), was introduced into peanut and cotton. In vitro bioassays using crude protein extracts from transgenic peanut and cotton plants and their progenies showed inhibition of A. flavus hyphal growth (Niu et al, 2009;Rajasekaran et al, 2008b). We have provided below examples of antifungal proteins and peptides showing efficacy in controlling A. flavus in maize.…”
Section: Enhancement Of Host Resistance Expression Of Antifungal Protmentioning
confidence: 96%
“…Significantly reduced lesion size was recorded in transgenic plants expressing a barley oxalate oxidase gene compared to the controls, which means that oxalate oxidase can confer enhanced resistance to Sclerotinia blight in peanuts (Livingstone et al, 2005). A non-heme chloroperoxidase gene (cpop) from Pseudomonas pyrrocinia, a growth inhibitor of mycotoxinproducing fungi, introduced into peanuts resulted in transgenic plants that showed inhibition of A. flavus hyphal growth and reduced aflatoxin contamination of peanut seeds (Niu et al, 2009).…”
Section: Transgenic Approach For Biotic Stress Managementmentioning
confidence: 99%
“…Rajasekaran et al (2000) reported that the expression of a chloroperoxidase gene from Pseudomonas pyrrocinia (cpo-p) in transgenic tobacco resulted in significant inhibition of Aspergillus flavus hyphal growth and reduced leaf anthracnose lesions caused by Colletotrichum destructivum. Recently, Niu et al (2009) also demonstrated the successful insertion and expression of the cpo-p gene derived from Pseudomonas pyrrocinia into the groundnut Arachis hypogaea. The developed transgenic groundnut plants showed inhibition of Aspergillus flavus hyphal growth, which resulted in the reduction of aflatoxin contamination in peanut seeds.…”
Section: Mycotoxinsmentioning
confidence: 99%